Material adaptation among rural primary school English language teachers - Mohd Iqbal Ahamat,; Muhammad Kamarul Kabilan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study is meant to investigate rural primary school teachers’ views on the use of imported textbooks and their adaptation strategies in dealing with foreign content in the prescribed materials. A qualitative approach was employed using semi-structured interviews, involving seven rural primary school English language teachers. The responses were orthographically transcribed and analysed using thematic analysis. The teachers disclosed that they did not have problems with the grammatical elements in the textbooks, but the cultural context needed to be locally presented to make the materials meaningful to their students. Teachers with fewer years of teaching experience, as opposed to experienced teachers, were found to be more innovative in their classrooms. Prospective research might better consider larger samples and employ a deliberate method of study for a better generalisation.